Take the lead [videorecording (DVD)] - Friedlander, Liz; Banderas, Antonio; Brown, Rob, 1984-; Woodard, Alfre, 1953- (New Line Home Entertainment : Distributed by Warner Home Video, 2006)
Pierre Dulane is a former professional ballroom dancer who volunteers to teach dance in the New York public school system. At first his background clashes with his students' tastes, but together Dulane and his students create a completely new style of dance.